Using digital simuation for electrical engineering education and research - Trinh, Trọng Chưởng (Journal of Technical Education Science, 2009)
In the training and research in electrical Engineering, Software System for Simulation of Electric Power in Real time is very important. Power engineering education is again a topic of great interest ever since the process of deregulating the power industry has been initiated. Selecting the simulation technology as a base for developing the computer exercises, the project has concentrated on the development and utilization of a variety of simulation environments. The use the free software in the teaching process for future engineer training about de virtual laboratory is very recommendable. This paper gives a sample of an overview on the electrical power software tools